2019
DOI: 10.1021/acs.langmuir.9b02476
|View full text |Cite
|
Sign up to set email alerts
|

A Most Enantioselective Chiral Surface: Tartaric Acid on All Surfaces Vicinal to Cu(110)

Abstract: Enantioselective chemistry on intrinsically chiral surfaces is the quintessential form of structure-sensitive surface chemistry, arising purely from the dissymmetry of the surface structure. Identification or design of chiral surface structures that maximize enantioselectivity for a given processes is extremely challenging because of the limited magnitude of the enantiospecific interaction energetics of chiral molecules with chiral surfaces. Using spherical Cu single crystals exposing surfaces with a continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…The simplest kinetic parameter extracted from the data is t 1/2 (hkl) , the time at which the local coverage drops to half its initial value (Figure 8B). 64 This clearly reveals the surface structure sensitivity of D-TA decomposition on all surfaces vicinal to Cu(110). From this map, one can identify the surface orientation (×) exhibiting the greatest value of Δt 1/2 = t 1/2 (hkl)-R − t 1/2 (hkl)-S , i.e., the greatest enantiospecificity.…”
Section: High Throughput Sampling Of Surface Structure Spacementioning
confidence: 88%
See 1 more Smart Citation
“…The simplest kinetic parameter extracted from the data is t 1/2 (hkl) , the time at which the local coverage drops to half its initial value (Figure 8B). 64 This clearly reveals the surface structure sensitivity of D-TA decomposition on all surfaces vicinal to Cu(110). From this map, one can identify the surface orientation (×) exhibiting the greatest value of Δt 1/2 = t 1/2 (hkl)-R − t 1/2 (hkl)-S , i.e., the greatest enantiospecificity.…”
Section: High Throughput Sampling Of Surface Structure Spacementioning
confidence: 88%
“…D) The structure of Cu­(14,17,2), the most enantiospecific surface for TA decomposition lying in the vicinity of Cu(110). Reproduced with permission from ref . Copyright 2019 American Chemical Society.…”
Section: Structure Sensitivity On Chiral Surfacesmentioning
confidence: 99%
“…This has also been observed in the case of TA and Asp decomposition on a Cu(110)AE141-S 4 C and Cu(111)AE141-S 4 C, respectively. 28,63 The analytical solution of eqn (1) allows expression of t (hkl) 1/2 in terms of k (hkl) e and k (hkl) i . 62 Given the condition that k (hkl) e c k (hkl) i , it can be shown that t 1=2 ffi p=2 ffiffiffiffiffiffiffiffi ffi k i k e p .…”
Section: Papermentioning
confidence: 99%
“…For this reason, a high throughput approach is needed to study comprehensively the kinetics of enantioselective reactions on chiral surface orientations spanning crystallographic orientation space. 28,29 Significant development and application of high throughput experimental methods has occurred over the last decade. This allows rapid collection and analysis of datasets spanning broad continuous parameter spaces.…”
Section: Introductionmentioning
confidence: 99%
“…Since their discovery, liposomes have been utilized as a model for many studies to understand their biophysical and biochemical properties and possible applications [ 61 ]. They have been used as model membrane systems to examine the primary nature of cell membranes [ 62 ], as drug delivery systems in pharmacology [ 63 , 64 , 65 ], in biochemistry [ 62 , 66 , 67 ], diagnostics [ 68 ], in imaging [ 69 , 70 ], molecular biology [ 71 ], food technology and cosmetic industries [ 72 , 73 , 74 ], microfluidic technologies [ 75 , 76 ], in analytical methods [ 67 ], as a template for the production of nanogels [ 77 ], as the Biolubricants carrier [ 78 , 79 , 80 ], and in tissue engineering and regenerative medicine [ 60 , 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%